Sensitization to Horse Allergens-Molecular Analysis Based on the Results of Multiparameter Tests - Rosada, Tomasz; Lis, Kinga; Bartuzi, Zbigniew; Ukleja-Sokołowska, Natalia (International journal of molecular sciences, 2025)
The domestic horse is the third most common source of animal allergens. Currently, five equine allergens have been classified (Equ c 1, 2, 3, 4, 6). Despite the apparently low exposure to allergens, equine allergy is still of great clinical importance. The aim of the study was to analyze equine allergy based on the results of ImmunoCAP ISAC and Allergy Xplorer ALEX tests. The study was retrospective. A total of 1553 patients were analyzed. Immunological tests were performed using the ImmunoCAP ISAC and Allergy Xplorer ALEX systems. From all the results, those with a positive result for at least one horse allergen were selected for further analysis. Horse allergy was found in 9% of subjects by the ImmunoCAP ISAC and in 10% by the Allergy Xplorer ALEX system. In both tests, sIgE for Equ c 1 was most frequently found. Horse allergy was very often accompanied by allergy to other animals. Monosensitization to horse was found only in the ImmunoCAP ISAC tests (0.2% of the population). In the ImmunoCAP ISAC tests, a correlation was found between Equ c 1 and Can f 1, Can f 2, Can f 5, Fel d 1, Fel d 4, Mus m1 and Can f 3; with increasing sIgE concentrations for the allergen Equ c 1, the results for the remaining correlated allergens increased. Horse allergy is a common clinical problem. Equ c 1 is the major horse allergen. Monosensitization to horse is rare. The present study is the first to present analyses of sIgE concentrations for horse allergens.